2020
DOI: 10.22146/mot.55173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Potential of Carbonated Hydroxyapatite Combined with Propolis on Porphyromonas gingivalis

Abstract: Carbonated hydroxyapatite is ideal as a bone graft material because it has similar organic matters to the bone, excellent osteoconductive properties, and good biodegradation in the body. Hydroxyapatite contains the risk of being contaminated by bacteria called Porphyromonas gingivalis (P. gingivalis) in the oral cavity because it has no vascularization, therefore, facilitating adhesion of bacteria, and when applied in the oral cavity, it may cause an infection that then inhibits healing. Thus, it is necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…5 6 , which loaded the propolis into the carbonated hydroxyapatite using the immersion method, found that the 10% propolis solution had the strongest chemical bond with carbonated hydroxyapatite. This experiment is in line with the study by Devitaningtyas et al 7 , which found that 10% propolis with carbonated hydroxyapatite had a strong antibacterial inhibition against P. gingivalis bacteria.…”
Section: Introductionsupporting
confidence: 92%
“…5 6 , which loaded the propolis into the carbonated hydroxyapatite using the immersion method, found that the 10% propolis solution had the strongest chemical bond with carbonated hydroxyapatite. This experiment is in line with the study by Devitaningtyas et al 7 , which found that 10% propolis with carbonated hydroxyapatite had a strong antibacterial inhibition against P. gingivalis bacteria.…”
Section: Introductionsupporting
confidence: 92%
“…10 A previous study showed that CHA immersed in 10% propolis solution had an excellent mechanical and chemical bond between the two materials, 11 and this new material showed excellent capability in stimulating fibroblast cell lines. 12 Devitaningtyas et al 13 proved the inhibition properties of CHA-10% propolis against Porphyromonas gingivalis. Another study of propolis-coated allograft bone graft material showed that propolis also has osteoinductive properties by stimulating the proliferation and differentiation of bone cells -thus accelerating the bone regeneration processes in experimental animals.…”
Section: Introductionmentioning
confidence: 99%